Upaya Guru dalam Meningkatkan Kemampuan Membaca Al-Qur’an Santri MDTA Baitul Makmur Kota Pekanbaru - Ibrahim, Dani; Wiza, Rahmi (YASIN, 2023)
The purpose of this study is to describe how the efforts made by the teacher in improving the ability to read the Koran of students in ahkamul mad wal qasr, makharijul huruf and ahkamul huruf in the Baitul Makmur MDTA Pekanbaru city. The research method used in this research is a qualitative descriptive research type. Data collection techniques using observation, interviews and documentation. The research subjects were madrasa teachers and third grade students of MDTA Baitul Makmur Pekanbaru. Based on the results of the study, it can be concluded that in improving the ability to read the Koran, students made several efforts, such as: using the tartil method, using the recitation method, using the sima'i method and visualizing material carried out by the teacher to make it easier for students to improve their reading ability.